Use of the flat panel detector fluoroscope reduces radiation exposure during periacetabular osteotomy - Rachael Martino; Patrick Carry; Jennifer Stickel; Omar Samara; Sterling Lee; Courtney Selberg (Scientific Reports, 2024)
Abstract The Periacetabular Osteotomy is a technically demanding procedure that requires precise intraoperative evaluation of pelvic anatomy. Fluoroscopic images pose a radiation risk to operating room staff, scrubbed personnel, and the patient. Most commonly, a Standard Fluoroscope with an Image Intensifier is used. Our institution recently implemented the novel Fluoroscope with a Flat Panel Detector. The purpose of this study was to compare radiation dosage and accuracy between the two fluoroscopes. A retrospective review of a consecutive series of patients who underwent Periacetabular Osteotomy for symptomatic hip dysplasia was completed. The total radiation exposure dose (mGy) was recorded and compared for each case from the standard fluoroscope (n = 27) and the flat panel detector (n = 26) cohorts. Lateral center edge angle was measured and compared intraoperatively and at the six-week postoperative visit. A total of 53 patients (96% female) with a mean age and BMI of 17.84 (± 6.84) years and 22.66 (± 4.49) kg/m2 (standard fluoroscope) and 18.23 (± 4.21) years and 21.99 (± 4.00) kg/m2 (flat panel detector) were included. The standard fluoroscope averaged total radiation exposure to be 410.61(± 193.02) mGy, while the flat panel detector averaged 91.12 (± 49.64) mGy (p < 0.0001). The average difference (bias) between intraoperative and 6-week postoperative lateral center edge angle measurement was 0.36° (limits of agreement: − 3.19 to 2.47°) for the standard fluoroscope and 0.27° (limits of agreement: − 2.05 to 2.59°) for the flat panel detector cohort. Use of fluoroscopy with flat panel detector technology decreased the total radiation dose exposure intraoperatively and produced an equivalent assessment of intraoperative lateral center edge angle. Decreasing radiation exposure to young patients is imperative to reduce the risk of future comorbidities.